Cut and fold paper textures : techniques for surface design - Jackson, Paul, 1956- (London : Laurence King Publishing, Ltd, 2017)
This book will show you inspirational ways in which paper can be used to create textured and relief surfaces. These techniques are mostly intuitive and easy to make, requiring no origami or paper engineering knowledge. There are 12 different techniques: Twisting narrow strips to make "paper string", Weaving strips, Layering, Coiling, Tearing, Bending, Incising and Lifting, Crumpling, Pleating, Cutting Pleats, Stippling and using Translucent Surfaces. Each is beautifully illustrated with creative examples, first made in white paper and then in papers of different colours, weights and textures. Finally, inspirational photographs show the techniques applied by designers to clothing, furniture, jewellery and homewares, as well as artworks.
1. Twisting -- 2. Weaving -- 3. Layering -- 4. Coiling -- 5. Tearing -- 6. Bending -- 7. Incising and Lifting -- 8. Crumpling -- 9. Pleating -- 10. Cut Pleats -- 11. Stippling -- 12. Translucent Surfaces.
Keywords: Paper work -- Technique; Paper art; Paper sculpture; Paper folding (Graphic design)